Gene expression meta-analysis reveals aging and cellular senescence signatures in scleroderma-associated interstitial lung disease - Yang, Monica M.; Lee, Seoyeon; Neely, Jessica; Hinchcliff, Monique; Wolters, Paul J.; Sirota, Marina (Frontiers in Immunology, 2024)
Aging and cellular senescence are increasingly recognized as key contributors to pulmonary fibrosis. However, our understanding in the context of scleroderma associated interstitial lung disease (SSc-ILD) is limited. To investigate, we leveraged previously established lung aging and cell-specific senescence signatures to determine their presence and potential relevance to SSc-ILD. We performed a gene expression meta-analysis of lung tissue from 38 SSc-ILD and 18 healthy controls and found markers (GDF15, COMP, CDKN2A) and pathways (p53) of senescence were significantly increased in SSc-ILD. When probing the established aging and cellular senescence signatures, we found epithelial and fibroblast senescence signatures had a 3.6-fold and 3.7-fold enrichment respectively in the lung tissue of SSc-ILD and that lung aging genes (CDKN2A, FRZB, PDE1A, NAPI12) were increased in SSc-ILD. These signatures were also enriched in SSc skin and associated with degree of skin involvement (limited vs. diffuse cutaneous). To further support these findings, we examined telomere length (TL), a surrogate for aging, in lung tissue and found independent of age, SSc-ILD had significantly shorter telomeres than controls in type II alveolar cells in the lung. TL in SSc-ILD was comparable to idiopathic pulmonary fibrosis, a disease of known aberrant aging. Taken together, this study provides novel insight into the possible mechanistic effects of accelerated aging and aberrant cellular senescence in SSc-ILD pathogenesis.